Contrast agents and ionization with respect to safety for patients and doctors - Tengg-Kobligk, Hendrik von (Patient safety in dialysis access, 2015)
In hemodialysis patients, radiographic imaging with iodinated contrast medium (ICM) application plays a central role in the diagnosis and/or follow-up of disease-related conditions. Therefore, safety